Accumulation of Heavy Metal Ions by Eichhornia Crassipes from Battery Industry Effluent under the Influence of Cattle Manure - Myilsamy, Dinesh kumar; Angamuthu, Sivalingam; Marimuthu, Thirumarimurugan (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Phytoremediation, an emerging technology which uses plants to remove contaminants of concern (COC) such as organic and inorganic compounds especially heavy metals (HM). The present study focuses on assessing the toxicity of heavy metals available in effluents discharged from industries and the accumulation ability of an aquatic plant, Eichhornia crassipes (water hyacinth). Phytoremedial potential of E. Crassipes and HM interaction between soil and water were evaluated in the present study under the presence of cow dung manure as an enhancer. Heterogenous accumulation of metal ions were found in the plant. Heavy metal concentration in plant parts were varied for roots and shoots. The concentration of HM ions in the plant parts were varied from root to shoot. Value of translocation factor (TF) was found to be in the region 0.5 – 0.8, with Fe has low (0.51) and Pb has high (0.77), bioconcentration factor (BCF) were in the order of Ar > Ca > Zn > Fe > Pb at both roots and shoots. Transposition factor (TrF) of all HM ions were >1.5 except for Zn (1.21). E. Crassipes was found to accumulate a large amount of HM ions and could be used for efficient treatment of contaminated water.